SPATIAL POLICY DILEMMA: ENVIRONMENTAL SUSTAINABILITY AND ECONOMIC GROWTH - Haris Budiman; Eman Suparman; Anis Mashdurohatun (UNTAG Law Review, 2018)
The regulation of spatial planning aims to meet the demands of the built-area and preserve the environment for sustainable urban development. Yet, the implementation of spatial planning for welfare and environmental sustainability faces various problems such as conflicts between sectors and regions. Similarly, the efforts to improve welfare through economic growth lead to land conversion that has an impact on environmental demage and land conflicts. The purpose of this study is to analyzethe factors inhibiting local governments in implementing the spatial planning. This research belongs to qualitative research with Socio Legal approach. The informants and respondents were chosen by applying purposive sampling technique, while the data validation used triangulation. The results showed that local governments have difficulties in implementing environmental-based spatial planning as well as increasing economic growth, especially for regions with small local revenues. Limited resources, inconsistenct policy, and weak regulation arrangements have become inhibiting factors in meeting the demands of environmental-based spatial planning and increasing economic growth. Therefore, commitment from local government is needed to solve the problem by increasing the capacity of government apparatus, enforcing the rules, and reconstructing the fair and prosperous spatial policy.